Effects of Vegetation Type and Management Practice on Soil Respiration of Grassland in Northern Japan - Minaco Adachi; Satoshi Tsuda (Applied and Environmental Soil Science)
Soil respiration rate in two types of grassland dominated with Zoysia japonica and Miscanthus sinensis, respectively, and under two management practices (undisturbed and intentionally burned) for the M. sinensis grassland was investigated for understanding the effects of grassland vegetation type and management practices on the relationship between soil temperature and soil respiration in northern Japan. Soil temperatures at depth of 1 cm in the Z. japonica (ZJ) and burned M. sinensis (MSb) plots had a larger temporal variation than that in the control M. sinensis (MSc) plot prior to early July. However, the coefficient of temperature sensitivity () values, based on soil respiration rates and soil temperatures at 5 cm depth in the ZJ and MSb plots, were 1.3 and 2.9. These rates were lower than that in the MSc plot (4.3), meaning that soil respiration showed lower activity to an increase in soil temperature in the ZJ and MSb plots. In addition, monthly carbon fluxes from soil in these plots were smaller than that in the MSc plot. These results suggested that artificial disturbance would decrease soil microbial or/and plant root respiration, and it would contribute to the plant productivity. Future studies should examine the effects of the intensity and period of management on the soil respiration rate.